Perbedaan Persepsi Antara Mahasiswa Pre-Klinik Dan Klinik Terhadap Midline Shifting Pada Gigi Tiruan Lengkap - Herry Makmur; Nova Adrian (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: Facial aesthetic is affected by components that can be observed from the face as a whole (macro-esthetics), and also from the dental components (micro-esthetics). Ideally, the dental midline of a complete denture should coincide with the facial midline of the wearer (i.e. no midline shifting). Among others, one of the main aims of using complete dentures for prosthodontics treatments is to improve facial aesthetic. Consequently, the ability and competency of a dentist to detect midline shifting is vital in order to attain a complete denture with optimal esthetics. In dentistry, the relationship between individual perception of midline shifting and the level of education is often studied. Apart from gender and age, other factors such as the level of education can influence individual’s perception towards midline shifting. The objective of this study is to find out the difference between the perception of pre-clinical and clinical students towards midline shifting in complete dentures. The type of study is cross-sectional observational analytic. Materials and Methods: This study involves 128 pre-clinical and clinical students in FKG Universitas Trisakti. The student’s perception towards midline shifting is measured using 9 photos and a questionnaire. Results: 128 dental students with equal distribution between pre-clinic and clinic students participated in this study. Data analysis showed difference of perception between the two groups (p-value 0.016). Conclusions: There is a significant difference between the perception of pre-clinical and clinical students in FKG Universitas Trisakti towards midline shifting in complete dentures.